Doing a systematic review : a student's guide - Boland, Angela; Cherry, M. G. (M. Gemma); Dickson, R. (Rumona) (Los Angeles : SAGE, 2017)
Structured around 10 key steps to complete the systematic review process, the new edition of the bestseller is the perfect guide to using the technique in a research project.
Rumona Dickson, M. Gemma Chery and Angela Boland -- Planning and managing my review / Gerlinde Pilkington and Juliet Hounsome -- Defining my review question and identifying inclusion and exclusion criteria / M. Gemma Cherry and Rumona Dickson -- Developing my search strategy / Yenal Dundar and Nigel Fleeman -- Applying inclusion and exclusion criteria / Yenal Dundar and Nigel Fleeman -- Data extraction: where do I begin / Nigel Fleeman and Yenal Dundar -- Quality assessment: where do I begin? / Janette Greenhalgh and Tamara Brown -- Understanding and synthesizing numerical data from intervention studies / Michaela Brown and Marty Richardson -- Writing my discussion and conclusions / M. Gemma Cherry -- Disseminating my review / M. Gemma Cherry and Gerlinde Pilkington -- Reviewing qualitative evidence / M. Gemma Cherry, Helen Smith, Elizabeth Perkins and Angela Boland -- Reviewing economic evaluations / Angela Boland, Sophie Beale and M. Gemma Cherry.
Includes bibliographical references and index.
Adult
Keywords: Research -- Methodology